JENIS-JENIS POHON PENYUSUN DI SEMPADAN KALI KUNING KALIURANG PASCA ERUPSI MERAPI 2010 - , DIANA HARTATI RAMBE ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The impacts of mount Merapi eruptions have caused damage to some forests on the slopes of Kali Kuning Kaliurang. Slopes which turned into river-border were a protected area and residentsâ land. The damage of stands on the banks of river-border caused its role and functions disturbed. The aim of this study was to determine the composition of tree species that made up the river-border of Kali Kuning after cold lava from mount Merapi flooded the area in 2010 and its differences in each zone. Data were collected through direct observation in the field by using nested sampling method. Plots measuring 20 m x 20 m were made a total of 18 PU to measure the level of living seedlings, saplings, poles, and trees. Manufacture of plots was done on the west and east sides of Kali Kuning in three zones namely upstream, midstream, and downstream. There were three plots which were close to the river, a little away from the river, and away from the river. The results of the study showed that after Merapi eruptions in 2010, river-border of Kali Kuning Kaliurang was grown by 23 types of vegetation that consisted of 8 types of seedlings level, 8 types of saplings level, 8 types of poles level and 15 types of tree level. In upstream zone, there were three types with the largest number namely Pinus merkusii, Piper aduncum, and Macaranga tanarius. The largest number was in central zone namely Swietenia macrophylla, Falcataria mollucana, and Gnetum gnemon, while downstream zone was dominated by Falcataria mollucana, Swietenia macrophylla, Calophyllum inophylum. Moreover, overall types of all age levels were: Swietenia macrophylla, Falcataria mollucana, Pinus merkusii, Leucaena leucocephala, Piper aduncum, Macaranga tanarius, Trema cannabina, Gnetum gnemon, Schima walichii, Hibsicus tiliaceus, Calophyllum inophyllum, Caliandra calothyrsus, Inocarpus fagiferus, Syzygium polyanthum, Muntingia calabura, Artocarpus heterophyllus, Acacia mangium, Dimocarpus longana, Delonix regia, Melia azedarach, Persea Americana, Pterosperum javanicum, Samanea saman.